A Description of the Temporal Pattern of Out-of-Pocket Expenditure Related to Iranian Healthcare Services during 1995-2014 - Masoud BEHZADIFAR; Tina BEYRANVAND; Mehdi JAFARI; Meysam BEHZADIFAR; Masood TAHERI MIRGHAED; Mariano MARTINI; Nicola Luigi BRAGAZZI (Tehran University of Medical Sciences, 2018)
Background: Out-of-pocket (OOP) expenditure directly impacts on poverty and household welfare, especially when there is a decline in healthcare financing. This study was aimed to describe the temporal pattern of OOP expenditures related to Iranian healthcare services during 1995-2014. Methods: For describing the trend of OOP spending in Iran, the database of the World Bank was mined for the period under study. Further, the trend analysis has been complemented by an exhaustive and comprehensive review of the extant literature. Results: From 1995 to 2014, out-of-pocket decreased from 53.59% to 47.8% of the total health expenditure, probably because of the different health reforms implemented throughout the years. However, out-of-pocket expenditure in Iran remains higher than the world average (roughly 3 times higher) Conclusion: It is an onus of the Iranian government to make serious attempts in order to reduce out-of-pocket expenditure, as well as to protect particularly poor and vulnerable subjects against catastrophic health expenditure. In order to ensure an equitable and affordable access to the healthcare system, decision- and policy-makers in Iran should implement a review of health care costs, insurance tariffs, and healthcare services packages covered by insurance organizations as well as introduce a progressive tax-based financing scheme as soon as possible.